Legal Services Regulation in Canada: Plus Ça Change? - Semple, Noel (2016)
In common law Northern Europe and in Australasia, a wave of reform has been transforming legal services regulation since roughly 1980. Old structures and approaches, based on the principles of professionalism and lawyer independence, are being replaced in these jurisdictions by new ones that prioritize competition and consumer interests. In the United States this has conspicuously not happened, leaving intact a regulatory approach whose broad outlines have changed little in the past 100 years.
Keywords: Noel Semple